Effects of 6‐meals‐a‐day feeding and 6‐meals‐a‐day feeding combined with adrenalectomy on daily gene expression rhythms in rat epididymal white adipose tissue. (15th November 2015) - Su, Yan; Foppen, Ewout; Zhang, Zhi; Fliers, Eric; Kalsbeek, Andries
Abstract : The master clock in the hypothalamic suprachiasmatic nucleus (SCN) is assumed to synchronize the tissue‐specific rhythms of the peripheral clocks with the environmental day/night changes via neural, humoral and/or behavioral connections. The feeding rhythm is considered an important Zeitgeber for peripheral clocks, as daytime feeding reverses (clock) gene rhythms in the periphery, but not in the SCN. In this study, we investigated the necessity of a daily feeding rhythm for maintaining gene expression rhythms in epididymal white adipose tissue (eWAT). We showed that 7 of 9 rhythmic metabolic/adipokine genes, but not clock genes, lost their rhythmicity upon exposure to 6‐meals‐a‐day feeding. Previously, we showed comparable effects of adrenalectomy on eWAT; therefore, subsequently we investigated the effect of simultaneous disruption of these humoral and behavioral signaling pathways, by exposing adrenalectomized animals to 6‐meals‐a‐day feeding. Interestingly, under these conditions, all the clock genes and 10 of 11 rhythmic metabolic/adipokine genes lost their rhythmicity. These data indicate that adrenal hormones and feeding rhythm are indispensable for maintaining daily rhythms in metabolic/adipokine gene, but not clock gene, expression in eWAT. In contrast, at least one of these two signals should be present in order for eWAT clock gene rhythms to be maintained. Abstract : We investigated the importance of adrenal hormones and a daily feeding rhythm as rhythmic outputs of the biological clock to synchronize day/night rhythms in (clock) gene expression in white adipose tissue (WAT). We found that at least one of these two outputs should be present in order for WAT clock gene rhythms to be maintained.